Variability and Character Association in ablab Bean - Rajora, M P; Yadav, M S (Annals of Arid Zone, 2016)
Variability, .corrleation and path-coefficient analyses were performed for seven characters in ten genotypes of labJab bean (Lablab purpureus (L) sweet). High genot pic as well as phenotypic coefficients of variation, high heritability and high genetic advance were observed for dry matter yield and green fodder yield. Dry matter yield was positively associated with plant height, number of primaIZ branches per plant, stem thickness and green fodder yield. Path analysis showed that number of primary branches per plant, plant height, stem thickness and Jeaf:stem ratio are the important characters contributing to dry matter yield.